Dynamic changes in circulating tumor DNA assessed by shallow whole‐genome sequencing associate with clinical efficacy of checkpoint inhibitors in NSCLC - Caterina Carbonell; Joan Frigola; Nuria Pardo; Ana Callejo; Patricia Iranzo; Augusto Valdivia; Ilaria Priano; Susana Cedrés; Alex Martinez‐Marti; Alejandro Navarro; Laura Lenza; Mireia Soleda; et al. (Molecular Oncology, 2023)
Immune checkpoint inhibitors (ICIs) targeting the PD‐1/PD‐L1 axis are the main therapeutic option for patients with advanced non‐small cell lung cancer (NSCLC) without a druggable oncogenic alteration. Nevertheless, only a portion of patients benefit from this type of treatment. Here, we assessed the value of shallow whole‐genome sequencing (sWGS) on plasma samples to monitor ICI benefit. We applied sWGS on cell‐free DNA (cfDNA) extracted from plasma samples of 45 patients with metastatic NSCLC treated with ICIs. Over 150 samples were obtained before ICI treatment initiation and at several time points throughout treatment. From sWGS data, we computed the tumor fraction (TFx) and somatic copy number alteration (SCNA) burden and associated them with ICI benefit and clinical features. TFx at baseline correlated with metastatic lesions at the bone and the liver, and high TFx (≥ 10%) associated with ICI benefit. Moreover, its assessment in on‐treatment samples was able to better predict clinical efficacy, regardless of the TFx levels at baseline. Finally, for a subset of patients for whom SCNA burden could be computed, increased burden correlated with diminished benefit following ICI treatment. Thus, our data indicate that the analysis of cfDNA by sWGS enables the monitoring of two potential biomarkers—TFx and SCNA burden—of ICI benefit in a cost‐effective manner, facilitating multiple serial‐sample analyses. Larger cohorts will be needed to establish its clinical potential.